The Relationship between Students Perceptions of the Science Learning Environment on the Learning Outcomes: Hubungan Persepsi Siswa Tentang Lingkungan Belajar IPA Terhadap Hasil Belajar Siswa - Ihsan Anwari; Noly Shofiyah (Indonesian Journal of Education Methods Development, 2018)
The purpose of this study was to describe students` perceptions of the science learning environment in class VII SMP Sepuluh Nopember, to describe student learning outcomes in class VII SMP Sepuluh Nopember, and whether there was a relationship between students` perceptions of the science learning environment and student learning outcomes in class VII SMP Sepuluh Nopember Sidoarjo. This type of research includes quantitative research with comparative causal types with correlation analysis techniques. Data collection was obtained through questionnaires and documentation of students cognitive learning outcomes,the sample used was 29 students. The object of the research was the seventh grade students at SMP Sepuluh Nopember Sidoarjo. The results showed that the students` perceptions of the science learning environment in the high category were 6 students, 18 students in the medium category and 5 students in the low category. And the cognitive learning outcomes of students with complete categories of 15 students and incomplete categories of 14 students. Then the calculation was carried out through the correlation hypothesis test, the results of this calculation obtained significant results, namely 0,237< 0,05 and significant 0,216< 0,05, so this indicated that there was a positive relationship between students` perceptions of the science learning environment and student cognitive learning outcomes.